GRI 1, GRI 2, GRI 3Pada Laporan Keberlanjutan Perusahaan Pada Sektor Transportasi Dan Logistic Yang Terdaftar Di BEI Periode 2024 - Chandwiaman Anugerah Harefa; Afnelya Putri (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
This study evaluates the extent to which the 2021 GRI (Global Reporting Initiative) Universal Standards—particularly GRI 1, GRI 2, and GRI 3—are applied in the sustainability reports of logistics and transportation companies listed on the Indonesia Stock Exchange in 2024. The research methodology combines content analysis with a quantitative descriptive approach. For each GRI item in the sustainability report, indicators are evaluated using a 0–2 assessment methodology. The analysis findings show differences in the level of disclosure, with most companies falling into the moderate category and implementation levels ranging from 66% to 79%. These results indicate that although current sustainability reporting procedures have been implemented, there is still room for improvement in several areas, particularly in terms of disclosure of key themes. In addition to serving as a guide for future research and sustainability reporting procedures, this study also provides an empirical summary of the use of GRI 2021 in this industry.